Silicon carbide reticular porous ceramic filter and preparation method thereof

By using one-step filling polymer template technology and precise control of carbon source during the preparation of ceramic filters, the hollow pillars and defects in ceramic filters are solved, and the mechanical properties and structural density of ceramics are improved.

CN119430998AActive Publication Date: 2025-02-14NANJING IKAKAT EMISSIONS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411741667.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art faces defects caused by hollow pillar formation and polymer template combustion when preparing high-performance mesh porous ceramic filters, which affect the strength, heat impact resistance and melt metal corrosion resistance of the ceramic.

Method used

The one-step polymer template technology of silicon-carbon slurry is used, and the fine regulation of the performance and microstructure of silicon carbide mesh porous ceramics is achieved through precise control of the carbon source.

Benefits of technology

The hollow pillar problems caused by insufficient slurry filling in the preparation of ceramic filters and the defect problems that may occur during polymer decomposition are overcome, and the mechanical properties and structural density of ceramics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430998A_ABST
    Figure CN119430998A_ABST
Patent Text Reader

Abstract

According to the silicon carbide net-shaped porous ceramic filter and the preparation method thereof provided by the invention, a silicon carbon slurry one-step filling polymer template technology is adopted, and fine regulation and control on the performance and microstructure of silicon carbide net-shaped porous ceramic are realized by accurately controlling a carbon source; therefore, the hollow pillar problem caused by insufficient slurry filling in the ceramic filter preparation process and the defect problem possibly occurring in the polymer decomposition process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic material preparation, and in particular to a silicon carbide mesh porous ceramic filter and a preparation method thereof. Background Art

[0002] Ceramic filters are indispensable in metal casting, especially in precision casting, and are used to remove solid inclusions from molten metal. In addition to stable chemical properties and free of polluting chemical components, filters should also have good mechanical properties and thermal shock resistance, and will not peel or fall off during the casting process to ensure and improve the performance of the casting. Silicon carbide mesh porous ceramics, with their excellent mechanical properties, chemical stability, high temperature strength and corrosion resistance, occupy an important position in many filter applications, especially in the molten metal purification process in the metal smelting industry.

[0003] At present, the methods for preparing porous silicon carbide ceramics include foaming, 3D printing and polymer template methods, etc. The polymer template method has become the preferred method for manufacturing industrial filters because it can produce porous silicon carbide ceramics with a reticular pore structure, high permeability and large specific surface area, and has the advantages of low cost, high efficiency and simple operation.

[0004] Nevertheless, the use of polymer templates to prepare high-performance mesh porous ceramics still faces many challenges. Among them, the formation of hollow pillars and defects generated during the combustion of polymer templates have a significant impact on the strength, thermal shock resistance and molten metal corrosion resistance of silicon carbide ceramics. Therefore, many studies are devoted to reducing these voids and defects to improve the performance of silicon carbide mesh porous ceramics.

[0005] One technique to improve the strength and thermal shock resistance of porous ceramics is to refill them with slurries of different viscosities; however, although multiple filling processes can partially fill the voids within the pillars, they cannot completely eliminate the defects, and repeated filling may introduce new interface defects, which can adversely affect the mechanical properties of the final product.

[0006] Another method is to apply vacuum infiltration technology to reduce voids and defects. Low-viscosity slurry is used to fill the voids in the silicon carbide pillars under a vacuum environment, which can enhance the strength of the silicon carbide mesh porous ceramics. However, due to high cost, complex operation and low efficiency, the application of vacuum infiltration in industrial production is greatly limited. Summary of the invention

[0007] The purpose of the present invention is to provide a silicon carbide mesh porous ceramic filter and a preparation method thereof in response to the problems existing in the prior art. The method adopts a one-step filling polymer template technology with silicon-carbon slurry, and achieves fine regulation of the performance and microstructure of the silicon carbide mesh porous ceramic by precisely controlling the carbon source, thereby overcoming the hollow pillar problem caused by insufficient slurry filling in the preparation of the ceramic filter and the defect problem that may occur during the polymer decomposition process.

[0008] According to a first aspect of the present invention, there is provided a method for preparing a silicon carbide mesh porous ceramic filter, comprising the following steps:

[0009] S1. Preparation of the first carbon sphere-PVA composite sol

[0010] Completely dissolving PVA powder in deionized water to obtain a PVA solution, and cooling the solution for later use;

[0011] Dispersing the first carbon ball powder in deionized water, and breaking the agglomeration of the first carbon balls by ultrasonic treatment or mechanical stirring to obtain a first carbon ball dispersion;

[0012] adding a coupling agent to the first carbon sphere dispersion to allow the coupling agent to react with the functional groups on the surface of the first carbon sphere to form a chemical bond, thereby obtaining a modified first carbon sphere dispersion;

[0013] Under the condition of ultrasonic treatment or mechanical stirring, slowly adding the modified first carbon sphere dispersion into the PVA solution, and continuing the ultrasonic treatment or mechanical stirring until the first carbon spheres are evenly dispersed, to obtain a first carbon sphere-PVA composite sol;

[0014] S2, adding mixed silicon carbide powder, metallic silicon powder, second carbon ball powder, dispersant and plasticizer to the first carbon ball-PVA composite sol obtained in step S1, and stirring evenly to obtain a mixed wet material; wherein the average particle size of the first carbon ball is much smaller than the average particle size of the second carbon ball;

[0015] S3, ball-milling, sieving and defoaming the mixed wet material obtained in step S2 to obtain silicon carbide slurry;

[0016] S4, immersing the polymer template in the silicon carbide slurry obtained in step S3, removing the excess slurry using a rotating disk, and then drying to obtain a ceramic blank;

[0017] S5, sintering the ceramic blank obtained in step S4 to obtain a silicon carbide mesh porous ceramic filter.

[0018] As an optional embodiment, the average particle size of the first carbon sphere is 50nm-200nm, the sphericity is greater than 0.8, and the specific surface area is greater than 200m2 / g; the average particle size of the second carbon sphere is 1μm-10μm.

[0019] As an optional implementation, the mass concentration of the PVA solution is 5% to 10%, and the mass concentration of the first carbon sphere dispersion is 60% to 80%.

[0020] As an optional embodiment, the amount of coupling agent added is 1% to 5% of the weight of the first carbon sphere.

[0021] As an optional embodiment, the coupling agent includes one or more of γ-aminopropyltriethoxysilane (APTES), γ-methacryloxypropyltrimethoxysilane (MPTS), γ-glycidyloxypropyltrimethoxysilane (GPTMS), vinyltrimethoxysilane (VTMS), di(butoxyacetoacetylacetonate)diisopropoxytitanate (Tyzor AA-75), isopropoxytriacryloxytitanium (IPT), zirconate isopropoxyacrylate, and polyethylene glycol diglycidyl ether (PEGDE).

[0022] As an optional embodiment, in the mixed wet material, the specific proportions of the components, calculated by mass percentage, are: 25% to 45% mixed silicon carbide powder, 15% to 35% metallic silicon powder, 5% to 15% compound carbon ball powder, 0.5% to 2% dispersant, 1% to 5% plasticizer, and 20% to 40% deionized water; wherein the compound carbon ball powder includes a first carbon ball powder and a second carbon ball powder.

[0023] As an optional implementation, the first carbon ball powder accounts for 30% to 50% of the mass of the compound carbon ball powder, and the second carbon ball powder accounts for 50% to 70% of the mass of the compound carbon ball powder.

[0024] As an optional embodiment, the mixed silicon carbide powder includes a first silicon carbide powder and a second silicon carbide powder, and the average particle size of the first silicon carbide powder is smaller than the average particle size of the second silicon carbide powder.

[0025] As an optional embodiment, the average particle size of the first silicon carbide powder is 1 μm to 5 μm, and the average particle size of the second silicon carbide powder is 20 μm to 40 μm.

[0026] As an optional embodiment, the mass ratio of the first silicon carbide powder to the second silicon carbide powder is (3:7) to (5:5).

[0027] As an optional implementation, the average particle size of the metallic silicon powder is 5 μm to 15 μm.

[0028] As an optional embodiment, the dispersant includes one or more of polyvinylpyrrolidone K30 (PVP-K30), polycarboxylates, tetramethylammonium hydroxide and isobutylene maleic anhydride copolymer.

[0029] As an optional embodiment, the plasticizer includes one or more of ethylene glycol, glycerol, polyethylene glycol and ethylene glycol monoethyl ether.

[0030] As an optional implementation, the polymer template has a porosity greater than 80% and a pore size of 0.5 cm to 2 cm, and includes polyurethane honeycomb foam, polystyrene honeycomb foam or polyethylene honeycomb foam.

[0031] According to a second aspect of the present invention, there is provided a silicon carbide mesh porous ceramic filter prepared by the aforementioned method.

[0032] As an optional embodiment, the filter has a porosity greater than 80%, a compressive strength greater than 3 MPa, and a fracture strength greater than 3000 J / m 2 .

[0033] It can be seen from the above technical scheme of the present invention that the preparation method of the silicon carbide mesh porous ceramic filter proposed by the present invention uses carbon balls with different particle sizes as the core carbon source, firstly prepares the carbon ball-PVA sol by in-situ one-step chemical coupling agent modification, improves the dispersibility of small-particle carbon balls, and makes the small-particle carbon balls evenly distributed between large-particle carbon balls, and finally improves the stability and thixotropy of the slurry by combining the compounding of large and small-particle carbon balls, so that the distribution and filling of the slurry in the polymer matrix are more balanced, thereby achieving a balance between the reaction rate and density during subsequent sintering;

[0034] During sintering, the excellent thixotropy of the slurry allows the slurry to be evenly filled in different positions of the polymer matrix, avoiding large defects caused by sintering; at the same time, large-size carbon balls generate thicker SiC whiskers, enhancing the strength and toughness of the final product, and small-size carbon balls evenly fill the pores between large-size carbon balls, providing more carbon sources to react with silicon to form more fine SiC whiskers, thereby forming a denser sintered body, improving the strength and hardness of the final product, and thus improving the mechanical properties of the final product; and, compounding carbon balls of different particle sizes can adjust the reaction rate, making the reaction more uniform, and the gas in the sintering process can be evenly discharged, avoiding the defects caused by pore blockage and agglomeration.

[0035] In this way, the problem of hollow pillars caused by insufficient slurry filling in the preparation of ceramic filters and the problem of defects that may occur during the decomposition of the polymer are overcome.

[0036] The preparation method of the invention is simple to operate, easy to control, low in cost, high in efficiency, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 1 is a macroscopic image of a silicon carbide mesh porous ceramic filter according to an example of the present invention.

[0038] Figure 2 2a and 2b are SEM images of the silicon carbide mesh porous ceramic filter of the present invention; wherein 2a and 2b are SEM images at different magnifications, respectively.

[0039] Figure 3 : is the XRD pattern of the silicon carbide mesh porous ceramic filter according to the example of the present invention.

[0040] Figure 4 Graph showing the rheological properties of silicon carbide slurry according to an example of the present invention. DETAILED DESCRIPTION

[0041] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0042] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0043] Compared with traditional carbon black and flake graphite, carbon spheres have excellent dispersion and rheological properties. The addition of carbon spheres can improve rheological properties and ensure a more balanced distribution of carbon sources in the polymer matrix. In addition, the high specific surface area and chemical activity of carbon spheres are conducive to the in-situ reaction of silicon and carbon, thereby producing more and evenly distributed SiC whiskers, effectively making up for material defects and improving the mechanical strength of ceramic materials.

[0044] However, the traditional process cannot completely solve the slurry dispersion and stability problems when using single-size carbon spheres as the carbon source. Therefore, it cannot effectively solve the hollow pillar problem caused by insufficient filling of the traditional slurry and the defect problem that may occur during the polymer decomposition process.

[0045] Therefore, the present invention mismatches carbon balls of different particle sizes and modifies small-size carbon balls. On the basis of changing the slurry properties, the carbon balls with mismatched particle sizes are combined to achieve a balance between reaction rate and density during sintering, thereby overcoming the above-mentioned problems. Through a simple and low-cost method, the mechanical properties of the silicon carbide mesh porous ceramic filter are improved while maintaining a high porosity.

[0046] In one exemplary embodiment of the present invention, a method for preparing a silicon carbide mesh porous ceramic filter is provided, comprising the following steps:

[0047] S1. Preparation of the first carbon sphere-PVA composite sol

[0048] Preparation of PVA solution: Dissolve an appropriate amount of PVA (polyvinyl alcohol) powder in deionized water, heat at about 90°C and stir continuously until the PVA is completely dissolved to form a uniform and transparent solution, then cool to room temperature for use.

[0049] Pre-dispersion treatment of the first carbon ball powder: the first carbon ball powder is dispersed in deionized water, and ultrasonic treatment or mechanical stirring is performed for 2 to 4 hours to break the agglomeration of the first carbon balls to obtain a first carbon ball dispersion.

[0050] In-situ introduction of coupling agent: adding the coupling agent into the first carbon sphere dispersion, stirring at 60-80° C. for 2-4 hours, allowing the coupling agent to react with the functional groups on the surface of the first carbon sphere to form chemical bonds, thereby obtaining a modified first carbon sphere dispersion.

[0051] Preparation of composite sol: Under the condition of ultrasonic treatment or mechanical stirring, the modified first carbon sphere dispersion is slowly added to the PVA solution, and the ultrasonic treatment or mechanical stirring (500-1000 rpm) is continued for 1-2 hours until the first carbon spheres are evenly dispersed to obtain the first carbon sphere-PVA composite sol.

[0052] S2. Add mixed silicon carbide powder, metallic silicon powder, second carbon ball powder, dispersant and plasticizer in sequence to the first carbon ball-PVA composite sol obtained in step S1, and stir evenly to obtain a mixed wet material; wherein the average particle size of the first carbon balls is much smaller than the average particle size of the second carbon balls.

[0053] S3. Pour the mixed wet material obtained in step S2 into a ball mill, and ball mill it at a speed of 200 r / min for 3 to 6 hours. Then, filter the slurry with a 100-mesh sieve, and use a vacuum centrifugal stirring degassing machine to remove bubbles to obtain silicon carbide slurry.

[0054] S4, immersing the polymer template in the silicon carbide slurry obtained in step S3, removing the excess slurry using a rotating disk, and then drying the template at 100° C. for 12 hours to obtain a ceramic blank.

[0055] S5. Sintering the ceramic blank obtained in step S4 at a temperature of 1450-1600° C. for 1-3 hours to obtain a silicon carbide mesh porous ceramic filter.

[0056] As an optional example, the average particle size of the first carbon spheres is in the nanometer level, and the average particle size of the second carbon spheres is in the micrometer level.

[0057] As an optional example, the average particle size of the first carbon sphere is 50 nm to 200 nm, the sphericity is greater than 0.8, and the specific surface area is greater than 200 m2 / g; the average particle size of the second carbon sphere is 1 μm to 10 μm.

[0058] As an optional example, the mass concentration of the PVA solution is 5% to 10%, and the mass concentration of the first carbon sphere dispersion is 60% to 80%.

[0059] As an optional example, the amount of the coupling agent added is 1% to 5% of the weight of the first carbon sphere.

[0060] As optional examples, the coupling agent includes one or more of γ-aminopropyltriethoxysilane (APTES), γ-methacryloxypropyltrimethoxysilane (MPTS), γ-glycidyloxypropyltrimethoxysilane (GPTMS), vinyltrimethoxysilane (VTMS), di(butoxyacetoacetylacetonate)diisopropoxytitanate (Tyzor AA-75), isopropoxytriacryloxytitanium (IPT), zirconate isopropoxyacrylate, and polyethylene glycol diglycidyl ether (PEGDE).

[0061] As an optional example, in the mixed wet material, the specific proportions of the components, calculated in terms of mass percentage, are: 25% to 45% mixed silicon carbide powder, 15% to 35% metallic silicon powder, 5% to 15% compound carbon ball powder, 0.5% to 2% dispersant, 1% to 5% plasticizer, and 20% to 40% deionized water; wherein the compound carbon ball powder includes a first carbon ball powder and a second carbon ball powder.

[0062] As an optional example, the first carbon ball powder accounts for 30% to 50% of the mass of the compound carbon ball powder, and the second carbon ball powder accounts for 50% to 70% of the mass of the compound carbon ball powder.

[0063] As an optional example, the mixed silicon carbide powder includes a first silicon carbide powder and a second silicon carbide powder, and the average particle size of the first silicon carbide powder is smaller than the average particle size of the second silicon carbide powder.

[0064] In a more specific example, the average particle size of the first silicon carbide powder is 1 μm to 5 μm, and the average particle size of the second silicon carbide powder is 20 μm to 40 μm.

[0065] As an optional example, the mass ratio of the first silicon carbide powder to the second silicon carbide powder is (3:7) to (5:5).

[0066] As an optional example, the average particle size of the metallic silicon powder is 5 μm to 15 μm.

[0067] As optional examples, the dispersant includes one or more of polyvinylpyrrolidone K30 (PVP-K30), polycarboxylates, tetramethylammonium hydroxide and isobutylene maleic anhydride copolymer.

[0068] As optional examples, the plasticizer includes one or more of ethylene glycol, glycerol, polyethylene glycol and ethylene glycol monoethyl ether.

[0069] As an optional example, the polymer template has a porosity greater than 80% and a pore size of 0.5 cm to 2 cm, and includes polyurethane honeycomb foam, polystyrene honeycomb foam or polyethylene honeycomb foam.

[0070] In the preparation method of the present invention, during the silicon carbide slurry preparation stage, the small-particle carbon spheres can increase the viscosity of the slurry due to their large specific surface area, reduce sedimentation, and thus enhance stability; in addition, the intermolecular force between the active groups on the surface of the small-particle carbon spheres and the binder PVA is strong, and this force can be weakened when subjected to external forces, and can be restored in a static state, thereby giving the slurry excellent thixotropy. However, the dispersibility of small-particle carbon spheres is poor, so some large-particle carbon spheres are used to replace them to ensure that the slurry can be stably and evenly dispersed while keeping the total carbon content unchanged, so that the slurry has good stability and thixotropy.

[0071] During the sintering stage, small-sized carbon spheres have a larger specific surface area and higher reaction activity, and can generate more fine silicon carbide whiskers, thereby improving the strength of the ceramic. However, the use of small-sized carbon spheres alone may cause uneven reaction and defects due to uneven dispersion of carbon spheres; at the same time, the rapid reaction of small-sized carbon spheres with silicon easily forms dense silicon carbide areas locally, which is not conducive to the removal of gases produced by the reaction and will also lead to defects. Therefore, introducing some large-sized carbon spheres into the system can, on the one hand, adjust the reaction rate, make the reaction more uniform, remove gases evenly, reduce the possibility of defects, and make the slurry fill the polymer template more evenly, reducing structural defects; on the other hand, large-sized carbon spheres can form more sturdy silicon carbide whiskers, thereby enhancing the toughness of the ceramic.

[0072] In another exemplary embodiment of the present invention, a silicon carbide mesh porous ceramic filter prepared by the above method is provided, wherein the porosity of the filter is greater than 80%, the compressive strength is greater than 3MPa, and the fracture strength is greater than 3000J / m 2 , while maintaining high porosity, it has excellent mechanical properties.

[0073] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0074] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0075] Example 1

[0076] (1) Preparation of small-size carbon sphere-PVA composite sol

[0077] a. Dissolve 2g of PVA (polyvinyl alcohol) powder in 25g of deionized water, heat at about 90°C and stir continuously until the PVA is completely dissolved to form a uniform and transparent solution, then cool to room temperature for use.

[0078] b. Pre-disperse 3.15 g of 100 nm carbon spheres in 4.5 g of water and stir mechanically for 3 h. Then add 0.09 g of APTES and stir at 60 °C for 2 h.

[0079] c. The PVA solution prepared in step a and cooled to room temperature is added with stirring to the small-particle carbon sphere suspension prepared in step b, and then stirred at 600 rpm for 2 h to obtain a small-particle carbon sphere-PVA composite sol.

[0080] (2) Add 21 g of 30 μm silicon carbide, 9 g of 5 μm silicon carbide, 25 g of 10 μm metal silicon powder, 6.85 g of 5 μm carbon ball powder, 0.5 g of PVP-K30, and 3 g of polyethylene glycol 400 to the composite sol prepared in step (1), and stir mechanically for 2 h.

[0081] (3) The wet material prepared in step (2) was poured into a ball mill and ball milled at a speed of 200 r / min for 4 h. The slurry was filtered through a 100-mesh sieve and defoamed using a vacuum centrifugal stirring degassing machine to prepare a silicon carbide slurry.

[0082] (4) Immerse a polyurethane honeycomb foam with an average pore size of 1 cm and a porosity of >85% into the slurry prepared in step (3), remove the excess slurry on the foam surface using a rotating disk at a rotation speed of 60 rpm, and then dry it at 100° C. for 12 hours to obtain a ceramic blank.

[0083] (5) The ceramic green body was sintered at 1500° C. for 2 h in a nitrogen atmosphere to prepare a silicon carbide mesh porous ceramic filter.

[0084] Comparative Example 1

[0085] [Direct blending of large and small size carbon spheres to prepare slurry]

[0086] The raw material quality composition is as follows:

[0087] Mixed silicon carbide powder: 30 g silicon carbide powder (21 g 30 μm silicon carbide, 9 g 5 μm silicon carbide);

[0088] 10μm metal silicon powder: 25g;

[0089] 100nm carbon ball powder 3.15g, 5μm carbon ball powder 6.85g;

[0090] PVA: 2g

[0091] PVP-K30: 0.5g

[0092] Macrogol 400: 3g

[0093] Deionized water: 29.5g

[0094] (1) Dissolve PVA powder in deionized water, heat at about 90°C and stir continuously until the PVA is completely dissolved to form a uniform and transparent solution, and then cool to room temperature for use.

[0095] (2) Add weighed silicon carbide powder, metallic silicon powder, carbon ball powder, PVP-K30, and polyethylene glycol 400 to the PVA solution prepared in step (1), and stir mechanically for 2 h.

[0096] (3) The wet material prepared in step (2) was poured into a ball mill and ball milled at a speed of 200 r / min for 4 h. The slurry was filtered through a 100-mesh sieve and defoamed using a vacuum centrifugal stirring degassing machine to prepare a silicon carbide slurry.

[0097] (4) Immerse the polyurethane honeycomb foam with an average pore size of 1 cm and a porosity of >85% into the slurry prepared in step (3), remove it from the foam surface using a rotating disk at a speed of 60 rpm, and then dry it at 100° C. for 12 hours to obtain a ceramic blank.

[0098] (5) The ceramic green body is sintered at 1500° C. for 2 h in a nitrogen atmosphere to prepare a silicon carbide mesh porous ceramic filter.

[0099] Comparative Example 2

[0100] [Using large-size carbon spheres alone]

[0101] The raw material quality composition is as follows:

[0102] Mixed silicon carbide powder: 30g silicon carbide powder (21g 30μm silicon carbide, 9g 5μm silicon carbide)

[0103] 10μm metal silicon powder: 25g

[0104] 5μm carbon ball powder 10g

[0105] PVA: 2g

[0106] PVP-K30: 0.5g

[0107] Macrogol 400: 3g

[0108] Deionized water: 29.5g

[0109] The preparation process is the same as that of Example 2 to obtain a silicon carbide mesh porous ceramic filter.

[0110] Comparative Example 3

[0111] [Using small-size carbon spheres alone]

[0112] The raw material quality composition is as follows:

[0113] Mixed silicon carbide powder: 30g silicon carbide powder (21g 30μm silicon carbide, 9g 5μm silicon carbide)

[0114] 10μm metal silicon powder: 25g

[0115] 100nm carbon ball powder 10g

[0116] PVA: 2g

[0117] PVP-K30: 0.5g

[0118] Macrogol 400: 3g

[0119] Deionized water: 29.5g

[0120] The preparation process is the same as that of Example 2 to obtain a silicon carbide mesh porous ceramic filter.

[0121] Comparative Example 4

[0122] [Carbon black as carbon source]

[0123] The raw material quality composition is as follows:

[0124] Mixed silicon carbide powder: 30g silicon carbide powder (30μm silicon carbide: 21g, 5μm silicon carbide 9g)

[0125] 10μm metal silicon powder: 25g

[0126] 1μm carbon black powder: 10g (carbon black powder: specific surface area 50-200m2 / g, bulk density: about 150-300kg / m3, particle size D50: 1μm)

[0127] PVA: 2g

[0128] PVP-K30: 0.5g

[0129] Macrogol 400: 3g

[0130] Deionized water: 29.5g

[0131] The ceramic preparation process is the same as in Example 2 to obtain a silicon carbide mesh porous ceramic filter.

[0132] Comparative Example 5

[0133] [Flake graphite as a carbon source]

[0134] The raw material quality composition is as follows:

[0135] Mixed silicon carbide powder: 30% silicon carbide powder (30μm silicon carbide: 21g, 5μm silicon carbide 9g)

[0136] 10μm metal silicon powder: 25g

[0137] 1μm flake graphite: 10g (graphite powder: specific surface area: 3-20m2 / g, bulk density: 200-600kg / m3, particle size D50: 1μm)

[0138] PVA: 2g

[0139] PVP-K30: 0.5g

[0140] Macrogol 400: 3g

[0141] Deionized water: 29.5g

[0142] The ceramic preparation process is the same as in Example 2 to obtain a silicon carbide mesh porous ceramic filter.

[0143] test

[0144] [SEM]

[0145] The filter of Example 1 was tested for morphology, and the results were as follows: Figure 1 and Figure 2 shown.

[0146] Combining the macroscopic and microscopic images, it can be seen that the filter has a mesh structure with a pore size of about 1 cm, which means that the prepared filter has a large flux and can effectively filter large-scale impurities in the metal melt.

[0147] [XRD]

[0148] The filter of Example 1 was subjected to XRD test, and the results were as follows: Figure 3 shown.

[0149] As can be seen from the figure, the prepared filter has the characteristic peaks of silicon carbide, which proves that a silicon carbide ceramic filter is obtained.

[0150] [Rheological properties of silicon carbide slurry]

[0151] The rheological properties of the slurry were measured using a rotational viscometer. Figure 4 shown.

[0152] As can be seen from the figure, the slurry prepared by preparing the small-size carbon sphere-PVA sol by in-situ one-step chemical coupling agent modification in Example 1 exhibits a higher viscosity at low shear rate, which prevents the sedimentation of particles, thereby ensuring the stability of the slurry. When the shear rate increases, the slurry viscosity decreases rapidly, showing good thixotropy, which promotes the rapid dilution of the slurry and the rapid filling of the foam pore wall during the impregnation process.

[0153] In Comparative Example 1, although the slurry prepared by directly blending large and small particle size carbon spheres exhibits higher viscosity at low shear rates and better thixotropy at high shear rates, the viscosity of the slurry is unstable due to the uneven dispersion of small particle size carbon spheres, which affects the consistency during actual filling.

[0154] In Comparative Example 2, the large-size carbon ball slurry alone was used, and the overall viscosity was low and the thixotropy was poor.

[0155] In Comparative Example 3, the overall viscosity of the slurry using small-particle carbon balls alone is relatively high, and the viscosity of the slurry is very unstable due to the poor dispersion of the small-particle carbon balls.

[0156] In Comparative Example 4, carbon black is used alone, and the overall viscosity of the slurry is low and the thixotropy is poor.

[0157] In Comparative Example 5, flake graphite is used alone, and the overall viscosity of the slurry is low and the thixotropy is poor.

[0158] [Porosity and Mechanical Properties]

[0159] The porosity, compressive strength and fracture strength of silicon carbide mesh porous ceramics were tested respectively, and the results are shown in the following table.

[0160] Porosity (%) Compressive strength(MPa) <![CDATA[Breaking strength J / m 2 > Example 1 81.5 3.14 3200 Comparative Example 1 83 2.5 2400 Comparative Example 2 89 1.14 1900 Comparative Example 3 86 1.21 1800 Comparative Example 4 87 1.12 1760 Comparative Example 5 89 1.04 1610

[0161] It can be seen from the table that the porosity of all samples reaches and exceeds 80%, so they all have excellent permeability.

[0162] Among them, the ceramic filter prepared in Example 1 has the lowest porosity, the highest compressive strength and the highest breaking strength.

[0163] The porosity of the ceramic filter in Comparative Example 1 increases, while the compressive strength and fracture strength both decrease. This is because direct blending leads to uneven distribution of local small-particle carbon balls. However, the compressive strength and fracture strength are higher than those in Comparative Examples 2 and 3, indicating that the compounding of large and small-particle carbon balls can effectively improve the strength of ceramics.

[0164] In Comparative Example 2, large-size carbon spheres are used alone, resulting in poor slurry stability and thixotropy, low reaction activity, and the generation of more large-size silicon carbide whiskers, so the porosity is the highest and the compressive strength is low.

[0165] In Comparative Example 3, small-size carbon spheres are used alone, and uneven dispersion leads to uneven local reaction and residual defects, which are manifested as high porosity and low strength.

[0166] In Comparative Example 4, carbon black is used alone, and uneven dispersion of the slurry leads to residual defects due to insufficient local carbon reaction, which manifests as high porosity and low strength.

[0167] In Comparative Example 5, flake graphite is used alone, and uneven dispersion of the slurry leads to residual defects due to insufficient local carbon reaction, which is manifested as high porosity and low strength.

[0168] It can be seen that a high-porosity and high-strength silicon carbide ceramic filter is successfully prepared by the method of the present invention.

[0169] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a silicon carbide mesh porous ceramic filter, characterized in that: The following steps are involved: S1. Preparation of the first carbon sphere-PVA composite sol Completely dissolving PVA powder in deionized water to obtain a PVA solution, and cooling the solution for later use; Dispersing the first carbon ball powder in deionized water, and breaking the agglomeration of the first carbon balls by ultrasonic treatment or mechanical stirring to obtain a first carbon ball dispersion; adding a coupling agent to the first carbon sphere dispersion to allow the coupling agent to react with the functional groups on the surface of the first carbon sphere to form a chemical bond, thereby obtaining a modified first carbon sphere dispersion; Under the condition of ultrasonic treatment or mechanical stirring, slowly adding the modified first carbon sphere dispersion into the PVA solution, and continuing the ultrasonic treatment or mechanical stirring until the first carbon spheres are evenly dispersed, to obtain a first carbon sphere-PVA composite sol; S2, adding mixed silicon carbide powder, metallic silicon powder, second carbon ball powder, dispersant and plasticizer to the first carbon ball-PVA composite sol obtained in step S1, and stirring evenly to obtain a mixed wet material; wherein the average particle size of the first carbon ball is much smaller than the average particle size of the second carbon ball; S3, ball-milling, sieving and defoaming the mixed wet material obtained in step S2 to obtain silicon carbide slurry; S4, immersing the polymer template in the silicon carbide slurry obtained in step S3, removing the excess slurry using a rotating disk, and then drying to obtain a ceramic blank; S5, sintering the ceramic blank obtained in step S4 to obtain a silicon carbide mesh porous ceramic filter.

2. The preparation method according to claim 1, characterized in that: The average particle size of the first carbon sphere is 50nm-200nm, the sphericity is greater than 0.8, and the specific surface area is greater than 200m2 / g; the average particle size of the second carbon sphere is 1μm-10μm.

3. The preparation method according to claim 1, characterized in that: The mass concentration of the PVA solution is 5% to 10%, and the mass concentration of the first carbon ball dispersion is 60% to 80%.

4. The preparation method according to claim 1, characterized in that: The added amount of the coupling agent is 1% to 5% of the weight of the first carbon sphere.

5. The preparation method according to claim 1, characterized in that: The coupling agent includes one or more of γ-aminopropyltriethoxysilane (APTES), γ-methacryloxypropyltrimethoxysilane (MPTS), γ-glycidyloxypropyltrimethoxysilane (GPTMS), vinyltrimethoxysilane (VTMS), di(butoxyacetoacetylacetonate)diisopropoxytitanate (Tyzor AA-75), isopropoxytriacryloxytitanium (IPT), zirconate isopropoxyacrylate, and polyethylene glycol diglycidyl ether (PEGDE).

6. The preparation method according to claim 1, characterized in that: In the mixed wet material, the specific proportions of the components are as follows, by mass percentage: 25% to 45% mixed silicon carbide powder, 15% to 35% metallic silicon powder, 5% to 15% compounded carbon ball powder, 0.5% to 2% dispersant, 1% to 5% plasticizer, and 20% to 40% deionized water; wherein the compounded carbon ball powder includes a first carbon ball powder and a second carbon ball powder.

7. The preparation method according to claim 6, characterized in that: The first carbon ball powder accounts for 30% to 50% of the mass of the compound carbon ball powder, and the second carbon ball powder accounts for 50% to 70% of the mass of the compound carbon ball powder.

8. The preparation method according to claim 6, characterized in that: The mixed silicon carbide powder includes a first silicon carbide powder and a second silicon carbide powder, wherein the average particle size of the first silicon carbide powder is smaller than the average particle size of the second silicon carbide powder.

9. The preparation method according to claim 8, characterized in that: The average particle size of the first silicon carbide powder is 1 μm to 5 μm, and the average particle size of the second silicon carbide powder is 20 μm to 40 μm.

10. The preparation method according to claim 8, characterized in that: The mass ratio of the first silicon carbide powder to the second silicon carbide powder is (3:7) to (5:5).

11. The preparation method according to claim 1, characterized in that: The average particle size of the metallic silicon powder is 5 μm to 15 μm.

12. The preparation method according to claim 1, characterized in that: The dispersant includes one or more of polyvinylpyrrolidone K30 (PVP-K30), polycarboxylates, tetramethylammonium hydroxide and isobutylene maleic anhydride copolymer.

13. The preparation method according to claim 1, characterized in that: The plasticizer includes one or more of ethylene glycol, glycerol, polyethylene glycol and ethylene glycol monoethyl ether.

14. The preparation method according to claim 1, characterized in that: The polymer template has a porosity greater than 80% and a pore size of 0.5 cm to 2 cm, and includes polyurethane honeycomb foam, polystyrene honeycomb foam or polyethylene honeycomb foam.

15. A silicon carbide mesh porous ceramic filter prepared by the method according to any one of claims 1 to 14.

16. The silicon carbide mesh porous ceramic filter according to claim 15, characterized in that: The filter has a porosity greater than 80%, a compressive strength greater than 3MPa, and a fracture strength greater than 3000J / m 2 .

Citation Information

Patent Citations

  • Multilevel pored foamed ceramic containing porous graphene microspheres and preparation method thereof

    CN107344855A

  • Preparation method of silicon carbide composite ceramic

    CN107778012A

  • Silicon carbide foamed ceramic and preparation method thereof

    CN113307629A

  • Silicon carbide nanofiltration membrane and preparation method thereof

    CN113856491A

  • Production of ceramic porous body

    JP2000109376A